GOKaRT: Graphical Online Search Tool for Maps - Schüler, Mechthild; Crom, Wolfgang (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2008)
The map department of the Staats- und Universitätsbibliothek Göttingen together with the Berlin State Library propose a project to develop a web-based graphic cataloguing and search system for maps, to be funded by the German Research Foundation. This tool shall be made available to all map holdings in archives, libraries, university departments and museums in Germany as a comfortable means for the administration of map holdings and as a search tool. Sheets belonging to map series as well as single maps (old and new) will be registered cooperatively by the participants with simple tools. This cooperation in data maintenance will facilitate the work especially for understaffed map holdings. Depending on the type of map there are four different mechanisms for map reference. For map series electronic index sheets are used which will show information regarding the various issues of the map sheets. Due to the intuitive graphic search entry GOKaRT-users will easily find the required maps of a certain region available in a chosen holding. User administration modules ensure comfortable handling. GOKaRT is being developed on the basis of licence-free open source programmes. In case financing is provided by the German Research Foundation, GOKaRT can be used free of charge internationally. This would require a contract stipulating data exchange between the partners as well as permanent storage and usability of the data.